one way is to solve for the invers of the first function
remembe, to solve, replace f(x) or g(x) with y, switch x and y, solve for y and replace it with f⁻¹(x)
A.
f(x)=x/2+8
y=x/2+8
x=y/2+8
x-8=y/2
2x-16=y
f⁻¹(x)=2x-16
nope, not A
B.
f(x)=3x³+16
y=3x³+16
x=3y³+16
x-16=3y³
(x-16)/3=y³
∛((x-16)/3)=y
f⁻¹(x)=∛((x-16)/3)
nope, not the same
not B
C.
f(x)=18/x-9
y=18/x-9
x=18/y-9
x+9=18/y
y(x+9)=18
y=18/(x+9)
f⁻¹(x)=18/(x+9)
correct, the answer is C
answer is C
not sure but you should use jiskha or photo math. hope this helps
Cos(θ) = -20/√((-20)^2 +(-21)^2)
.. = -20/-√841 . . . . . . . . . . . . . . . . . θ is a 4th-quadrant angle, so cos(θ) > 0
.. = 20/29
The value of the cosine is 20/29.
Answer: x= -2
Step-by-step explanation: first step is to add 7 to both sides. You’re left with -6x-22=5x. After this you’re going to add 6 to both sides. You get -22=11x. Now you divide both sides by 11 to get X by itself. You’re left with -2.